Green hydrogen in the European Union: a necessary path for the energy transition - López Antoranz, Juan (Revista Española de Desarrollo y Cooperación, 2021)
Green hydrogen represents a key asset to complement the deployment of renewable energies and offers multiple opportunities to decarbonise sectors that remain difficult to electrify, to contribute to the integration of the energy system and develop international trade and technological cooperation networks. The European Union has recently led several initiatives in the field of emissions reduction and energy transition, incorporating green hydrogen among its priorities and investment plans. Still under development, this energy vector could be crucial to attain the Sustainable Development Goals (SDG) of the 2030 Agenda.